Sumagang - Filio, Chanelle Niebres 1991- (2012)
""Sumagang" (in direct translation to Filipino can mean "sunrise" or "rising sun" is a thirteen-minute short film about a disheartened young man, Carl's recount on one of his journey from his hike in the mountains, to escape from his problems. He sees the mountains to be a realm where he might get rid of his burden of self. But, some mishaps compelled him to stay several days with the indigenous people called Agta. As he immersed with the indigenous tribe, he discovers the impossibility to escape, and that the place has also ills of their own, the only thing to do is to transcend and look on a different perspective. The film uses two theories: theory of Orientalism, in which, the people from the West have tendency to escape from its current ills, and to seek solace, however unrealistic and evanescent, in imaginary worlds elsewhere, a longing for a timeless state of being that transcends the painful divisions of this world. (Clarke, John James, 1997:19) and Existentialism. The two perspective applies on the film, with its elements on an individual that searches for a freedom from the bleakness of human existence on a realm that he thinks will help him escape his problems, but his choices of circumstances lead him to be introduced to the indigenous people- Agta, who dwells in that place. There he discovered that the place also suffers in the ills of their own and somehow mirrored his disputes, and he realizes that escape is neither the solution nor the answer."